Efektivitas Model Pembelajaran Atletik Berbasis Permainan Terhadap Motivasi Belajar Lari Sprint Siswa SMP Negeri 1 Makassar - Suriah Hanafi (Jurnal Inovasi Olahraga, 2026)
Purpose of the study: This study aimed to determine the effectiveness of the game-based athletic learning model on students' motivation to learn sprint running. Materials and methods: The research method used was a quantitative experiment with a One Group Pretest-Posttest Design. The subjects of this study were 32 students of SMP Negeri 1 Makassar, selected using a purposive sampling technique. The research instrument used was a learning motivation questionnaire that had been tested for validity and reliability (r = 0.87). Data were analyzed using normality test, homogeneity test, and paired sample t-test. Results: The results showed that there was a significant difference between the pretest and posttest values (t = -8.642; p = 0.000 < 0.05), indicating that the game-based athletic learning model was effective in improving students' learning motivation in sprint running. The average posttest score (76.45) was higher than the pretest (62.18) with an increase of 14.27 points (22.95%). Conclusions: These findings indicate that the integration of game elements in athletic learning can be an alternative approach in physical education learning to increase student motivation, especially in sprint running material.